HUBUNGAN KOMUNIKASI TERAPEUTIK PERAWAT RUANG PERAWATAN BEDAH DENGAN KECEMASAN PASIEN PRE OPERASI DI RSUD TAMAN HUSADA BONTANG - Salmah Salmah; Dwi Prihatin Era; Indah Nur Imamah (Bajang Institute, 2023)
Background : Preoperative anxiety is widespread, and the prevalence of preoperative anxiety reported in patients undergoing various types of surgery is 60-90%. A study conducted in Rwanda showed that clinically significant preoperative anxiety occurred in 72.8% of surgical patients. In Nigeria, the prevalence of preoperative anxiety in adult patients is 51%. To be able to increase the patient's confidence in facing a surgery, one way that must be done is that the nurse's therapeutic communication relationship with the patient needs to be built so that the patient can choose a positive coping alternative for himself. Objective : This study aims to determine the relationship between therapeutic communication of surgical nurses with anxiety of preoperative patients at Taman Husada Bontang Hospital. Methods : The research design used a cross sectional approach. Purposive sampling totaled 66 people. Data collection using the HARS anxiety questionnaire and therapeutic communication questionnaire . And analyzed with chi square test. Results : The results of good category nurse therapy communication were obtained from 54 respondents (81.8%). Preoperative patient anxiety at Taman Husada Bontang Hospital was obtained to experience the most mild anxiety, which was 65 respondents (98.5%). There was no statistical relationship between therapeutic communication of surgical nurses and preoperative patient anxiety at Taman Husada Bontang Hospital (p value 0.635).